Temporal overexpression of IL‐22 and Reg3γ differentially impacts the severity of experimental autoimmune encephalomyelitis. Issue 1 (16th May 2021) - Eken, Ahmet; Erdem, Serife; Haliloglu, Yesim; Zehra Okus, Fatma; Cakir, Mustafa; Fatih Yetkin, Mehmet; Akcakoyunlu, Merve; Karayigit, Mehmet Onder; Azizoglu, Zehra Busra; Bicer, Ayten; Gur, Tugba Nur; Aslan, Kubra; et al.
Abstract: IL‐22 is an alpha‐helical cytokine which belongs to the IL‐10 family of cytokines. IL‐22 is produced by RORγt+ innate and adaptive lymphocytes, including ILC3, γδ T, iNKT, Th17 and Th22 cells and some granulocytes. IL‐22 receptor is expressed primarily by non‐haematopoietic cells. IL‐22 is critical for barrier immunity at the mucosal surfaces in the steady state and during infection. Although IL‐22 knockout mice were previously shown to develop experimental autoimmune encephalomyelitis (EAE), a murine model of multiple sclerosis (MS), how temporal IL‐22 manipulation in adult mice would affect EAE course has not been studied previously. In this study, we overexpressed IL‐22 via hydrodynamic gene delivery or blocked it via neutralizing antibodies in C57BL/6 mice to explore the therapeutic impact of IL‐22 modulation on the EAE course. IL‐22 overexpression significantly decreased EAE scores and demyelination, and reduced infiltration of IFN‐γ+IL‐17A+Th17 cells into the central nervous system (CNS). The neutralization of IL‐22 did not alter the EAE pathology significantly. We show that IL‐22‐mediated protection is independent of Reg3γ, an epithelial cell‐derived antimicrobial peptide induced by IL‐22. Thus, overexpression of Reg3γ significantly exacerbated EAE scores, demyelination and infiltration of IFN‐γ+IL‐17A+ and IL‐17A+GM‐CSF+Th17 cells to CNS. We also show that Reg3γ may inhibit IL‐2‐mediated STAT5 signalling and impair expansion of Treg cells in vivo and in vitro . Finally, Reg3γ overexpression dramatically impacted intestinal microbiota during EAE. Our results provide novel insight into the role of IL‐22 and IL‐22‐induced antimicrobial peptide Reg3γ in the pathogenesis of CNS inflammation in a murine model of MS. Abstract : IL‐22 overexpression provides mice partial protection from EAE, underlining a therapeutic potential in human MS disease. This protection appears to be independent of Reg3γ. Our results also reveal that Reg3γ may directly and negatively regulate the function of Treg cells via STAT5‐mediated pathway; thus, its overexpression resulted in reduced Treg cell numbers and a more severe EAE course. ​